Northern Khanty demonstratives: a markedness-based approach - Marinina, Lera (Proceedings of the Amsterdam Colloquium, 2024)
This paper presents a semantic analysis of the Northern Khanty demonstratives. Northern Khanty has a tripartite demonstrative system: proximal term tăm, distal term tum and unmarked one śi. All terms may be used both exophorically and anaphorically. Based mainly on Ahn’s (2022) and Reisinger and Huijsmans’ (2021) approaches to the demonstratives, I account for the data postulating allosemy and presuppositions of different strengths for Northern Khanty demonstratives.